UMP's science and technology carnival promoted innovative culture - UMP, PNC

(untitled)
Universiti Malaysia Pahang (UMP)'s Faculty of Industrial Sciences & Technology (FSTI) organised a Science and Technology Carnival (ez-SciMaT), with cooperation from Ministry of Science, Technology and Innovation (MOSTI) recently.